An integrated sustainable tourism development strategy for the Vredefort Dome as a world heritage site - Coetzee, Willem Johannes Lourens (North-West University, 2004)
In order for the Vredefort Dome to be declared, and to exist as a World Heritage site, it is imperative that the tourism product owners in the area realise their roles as custodians of this precious site. This proposition leads to the main aim of this study, namely to develop an integrated tourism development strategy for the Vredefort Dome as a proposed World Heritage site. In order to achieve the above-mentioned aim, a thorough literature review was conducted. The goal of the literature study was to investigate the birth and growth of sustainable development based on Agenda 21. This literature review revealed that the three-legged chair of sustainable development has more profound foundations than the obvious economical, social and environmental aspects. Each one of these aspects consists of various elements that are interrelated. In order to formulate a strategy for sustainable tourism development, this interrelation between aspects was analysed and the following conclusions were drawn: Sustainable tourism development is an integrated system Education, poverty alleviation, health and insight into human settlements and demographics are the cornerstones of social well-being Climate change, land resources, deforestation, drought, mountain development, agriculture, biodiversity, freshwater resources, toxic chemicals and waste are central concerns in environmentally sensitive development 0 Institutions involved such as the different levels of Government, as well as aspects such as fair trade, economic enhancement programmes and economic measuring are essential elements of economic sustainability. The custodians of the present generation in the Vredefort Dome should realise their role in this complicated and integrated system and therefore the practices at present were evaluated as well as the future view regarding sustainable practices. In order, then, for sustainable tourism development to realise in the Vredefort Dome, the following strategies were formulated to assist product owners to achieve sustainability: Assisting to alleviate poverty in the VFD with a view to a sustainable future and supporting sustainable livelihoods Improving participation that would be true to the demographic composition in the VFD Protecting and promoting human health in the VFD Promoting education and training in the VFD Promoting sustainable human settlement development in the VFD-area Following an integrated approach to the planning and management of land resources Promoting sustainable agriculture and rural development Conserving the biological diversity in the VFD Acquiring support from national, provincial and local levels of government Establishing a system that guarantees supply that is coherent with fair trade in tourism Establishing an economic enhancement system that will contribute to the well-being of the VFD community Reducing leakage and other purchasing practices. The results of the empirical study indicated that tourism stakeholders are prepared to improve the present situation in the Vredefort Dome and are willing to adjust their businesses practices in the future. These changed practices addressed some strategic issues and the strategies above would give direction to this proposed World Heritage site to become more sustainable.
Thesis (Ph.D. (Tourism))--North-West University, Potchefstroom Campus, 2004.
Keywords: Sustainable; Tourism; Development; Integrated development